Clinical study and post operative outcomes of tympanostomy tube insertion in otitis media with effusion - Kumar, Ashutosh S.; Mahajan, Gundappa D.; Thomas, James; Sonar, Tejal A. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Otitis media with effusion (OME) is defined as the presence of a middle ear effusion in the absence of infection. Fluid in the middle ear is associated most commonly with a conductive hearing loss and an increased risk of acute middle ear infection. It can have an impact on quality of life. The objective of our study was to assess symptomatology of OME, study complications following tympanostomy tube insertion in OME and to highlight the age, sex distribution of otitis media with effusion. Methods: This prospective study was conducted in Department of Otorhinolaryngology, Dr. D. Y. Patil Medical College and Hospital, Pimpri, Pune from October 2017 to March 2019. 50 ears of patients aged between 6 to 50 years with OME were included in the study. All the patients were observed for symptomatology and postoperative complications who underwent Tympanostomy tube insertion. Results: OME is commoner in children and adolescents with no gender preponderance. The most common otoscopic findings pre-operatively included dull lustreless amber colored tympanic membrane in 56% (n=28), Retracted Tympanic Membrane and for shortened handle of malleus in 28% (n=14), air bubbles were seen in 12% (n=6) whereas fluid level was seen in 4% (n=2). Common complications post operatively included myringosclerosis and tympanic membrane atelectasis seen in 10% and 6% respectively. Conclusions: Tympanostomy tube insertion is one of the ideal treatments in management of otitis media with effusion, most commonly affecting younger age groups, with fewer complications, which can lead to a better quality of life.